Risk for Premature Mortality and Intentional Self-harm in Autism Spectrum Disorders - Jokiranta-Olkoniemi Elina; Gyllenberg David; Sucksdorff Dan; Suominen Auli; Kronström Kim; Chudal Roshan; Sourander Andre (Springer, 2022)
To examine the risk for premature mortality and intentional self-harm in autism spectrum disorders (ASD). Based on a national birth cohort. Children born in 1987-2005, diagnosed with ASD by 2007 (n = 4695) were matched with four non-ASD subjects (n = 18,450) and followed until 2015 for mortality and intentional self-harm. The risk among ASD subjects was elevated only for natural cause of death. The risk for intentional self-harm was increased in the unadjusted analyses, but decreased to non-significant after adjusting for comorbid psychiatric disorders. ASD subjects are at increased risk for premature mortality due to natural causes of death. While ASD subjects die of suicide and present with more self-harm, the association is explained by comorbid psychiatric disorders.